2016
DOI: 10.1016/j.devcel.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Slit-Robo Repulsive Signaling Extrudes Tumorigenic Cells from Epithelia

Abstract: SUMMARY Cells dynamically interact throughout animal development to coordinate growth and deter disease. For example, cell-cell competition weeds out aberrant cells to enforce homeostasis. In Drosophila, tumorigenic cells mutant for the cell polarity gene scribble (scrib) are actively eliminated from epithelia when surrounded by wild-type cells. While scrib cell elimination depends critically on JNK signaling, JNK-dependent cell death cannot sufficiently explain scrib cell extirpation. Thus, how JNK executed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 67 publications
3
116
0
Order By: Relevance
“…One of the best known roles of Robo signaling is its effect on the cells cytoskeleton (Blockus and Chedotal, 2016; McConnell et al, 2016; Vaughen and Igaki, 2016). Results from our microarray further supported the hypothesis that Slit/Robo signaling has a wider effect on neural crest cells cytoskeleton than previously thought.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the best known roles of Robo signaling is its effect on the cells cytoskeleton (Blockus and Chedotal, 2016; McConnell et al, 2016; Vaughen and Igaki, 2016). Results from our microarray further supported the hypothesis that Slit/Robo signaling has a wider effect on neural crest cells cytoskeleton than previously thought.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings by Vaughen and Igaki in Drosophila further supports this hypothesis. They present data that demonstrates a role for Slit/Robo via E-cadherin (E-cad) deregulation in extruding tumorigenic cells from epithelia (Vaughen and Igaki, 2016). Their findings help to explain how Slit/Robo signaling acts both as tumor suppressor and/or promoter in variety of cancers, and how this can be applied to the process of NCC becoming migratory upon delamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In flies, Slit/Robo signaling inhibits the formation of cadherin-mediated cell-cell junctions during heart development (Santiago-Martinez et al 2008). An interesting recent study in Drosophila provides evidence that Slit/Robo repellent signaling through JNK extrudes tumorigenic cells from epithelia by disrupting E-cadherin function (Vaughen and Igaki 2016). The investigators found that overexpression of Slit/Robo2 results in cells being dislocated from the epithelial surface, resulting in tumor formation within the luminal space.…”
Section: Slit-robo Regulation Of Adherens Junctionsmentioning
confidence: 99%
“…The investigators found that overexpression of Slit/Robo2 results in cells being dislocated from the epithelial surface, resulting in tumor formation within the luminal space. In contrast, loss of Slit/Robo2 signaling prevents cell extrusion, leading to tumor growth within the epithelium (Vaughen and Igaki 2016). In this way, the investigators propose that both over-and underactivation of Slit/Robo2 signaling contributes to tumorigenesis and cancer progression.…”
Section: Slit-robo Regulation Of Adherens Junctionsmentioning
confidence: 99%